2002
DOI: 10.1038/sj.npp.1300067
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cocaine on c-Fos and NGFI-B mRNA Expression in Transgenic Mice Underexpressing Glucocorticoid Receptors

Abstract: Numerous evidences suggest that stress and stress-related hormones can modulate the activity of the brain reward pathway and thus may account for individual vulnerability towards the reinforcing effects of drugs of abuse. Transgenic (TG) mice expressing an antisense mRNA against the glucocorticoid receptor (GR), which partially blocks GR expression, were used to assess the role of GR dysfunction on cocaine (COC)-induced c-fos and Nerve-Growth Factor Inducible-B (NGFI-B, or Nur77) gene expression. These two gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 55 publications
0
18
1
Order By: Relevance
“…Psychostimulants, such as AMPH and cocaine, strongly induce Nur77 expression in striatal cells (Bhardwaj et al 2003;Gonzalez-Nicolini and McGinty 2002;St-Hilaire et al 2003;Werme et al 2000). We previously observed that Nur77 gene knockout and RXR antagonist treatment were associated with exacerbated D 2 antagonist responses in mice (Beaudry et al 2000;Ethier et al 2004a, b).…”
Section: Discussionmentioning
confidence: 95%
“…Psychostimulants, such as AMPH and cocaine, strongly induce Nur77 expression in striatal cells (Bhardwaj et al 2003;Gonzalez-Nicolini and McGinty 2002;St-Hilaire et al 2003;Werme et al 2000). We previously observed that Nur77 gene knockout and RXR antagonist treatment were associated with exacerbated D 2 antagonist responses in mice (Beaudry et al 2000;Ethier et al 2004a, b).…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, Nur77 and Nor-1 are highly expressed in target areas of DA neurons, such as the striatal complex and prefrontal cortex (Beaudry et al 2000;Werme et al 2000a;Zetterström et al 1996). In these areas, strong modulation of Nur77 and Nor-1 has been observed after manipulation of DA neurotransmission with DA receptor antagonists (neuroleptics) or psychostimulants, or after DA denervation (Beaudry et al 2000;Ethier et al 2004a;St-Hilaire et al 2003a;2003b;Werme et al 2000a;2000b). In addition, we have shown that Nur77-deficient mice had an altered response after treatment with antipsychotic drugs (Ethier et al 2004a;2004b).…”
mentioning
confidence: 83%
“…These effects are reminiscent to the behavioural sensitization induced by psychostimulants in schizophrenic patients [34,35]. Nur77 and Nor-1 mRNA levels are also correlated with behavioural manifestations associated with cocaine and morphine administration (Table 1) [17,36,37].…”
Section: Nur77 and Rxr In Schizophrenia Model And Antipsychotic Drug mentioning
confidence: 99%